PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI CV DWI SPORT EKATAMA - Yuda Prayuda; Elliv Hidayatulah Lailiyah (Jurnal Pijar, 2026)
Employee performance at CV Dwi Sport Ekatama is influenced by the work environment and work motivation, as revealed in this study. A total of 30 employees participated as respondents in a survey that used a quantitative approach. Data were collected through a Likert-scale questionnaire and then analyzed using SPSS through a series of validity, reliability, classical assumption, and multiple linear regression tests. A conducive work environment and internal drive from within have proven to have a positive impact on employee performance. Worker performance increases significantly when they work in a safe, comfortable atmosphere supported by complete facilities. Work productivity is also driven upward due to the fulfillment of these two factors. Meanwhile, work motivation encourages increased responsibility, discipline, and quality of task completion. Together, these two variables produce a significant impact on employee performance, with the work environment being the most dominant factor. These results reinforce the idea that steps to improve employee performance should be directed toward creating a supportive work atmosphere and strengthening work motivation so that the achievement of company goals can be maximized